LDCs and world monetary reform - Karl-Heinz Sohn (Intereconomics, 1973)
A link between the creation of Special Drawing Rights and the financing of development aid is under discussion in order to meet the developing countries' demands for an adequate supply with international liquidity. This article expounds critically a number of objections raised against this concept.
Keywords: 330; Monetary Policy